THE EFFECT OF PROCESSING METHODS ON THE NUTRITIONAL QUALITY OF AFRICAN BREADFRUITS (TRECULIA AFRICANA) SEEDS - Nwozo Sarah Onyenibe; Julius Oluwaseun Oluwafunmilola; Stanley Udogadi Nwawuba (Indonesian Association of Food Technologists, 2019)
The extracted seeds of African breadfruit are identified to be extremely healthy whenever it is correctly processed. Therefore, the aim of the present study was to evaluate the effects of processing methods on the nutritional quality of African breadfruit seed. A qualitative phytochemical analysis including: Alkaloid, Flavonoid, Saponin, Tannin, Anthraquinone, Terpenoids, Steroid, and Cardiac Glycosides for the different fraction of African breadfruit seed was performed using a standard method. The result revealed the presence and greater amount of phytochemical for the raw fraction; seven in eight, six in eight for steamed fraction, and four in eight for boiled and roasted respectively. Anti-nutrient, Proximate, and Mineral Content were also conducted using standard methods. The amino acid composition was determined using High-Performance Liquid Chromatography (HPLC). The results of the present study revealed that anti-nutrients including Phytate, Tannins, and Oxalate were significantly p<0.05 reduced in the boiled fraction 5.47±0.15, 3.42±0.02 and 6.89±0.05, and highest in the raw fraction 7.77±0.01, 5.09±0.03 and 9.34±0.14. The proximate composition including; percentage crude fat, Ash, Carbohydrate, Fatty acid, and Energy value were significantly lower p<0.05 in the boiled fraction relative to the other fractions. Mineral contents; calcium, magnesium, sodium, potassium, and phosphorus were also significantly p<0.05 elevated in the boiled fraction relative to the raw, steamed, and roasted fraction. The amino acid composition was highest in the roasted and boiled fraction 57.350 and 56.978, and lowest in the steamed and raw fraction 35.754 and 28.748 respectively. Therefore, boiling (cooking) is encouraged for the preparation of African breadfruit seed.